Anatomical variations of the cystic artery: comparison of corrosion liver casts and laparoscopic cholecystectomies: Anatomske variacije cistične arterije: primerjava korozivnih jetrnih preparatov z laparoskopskimi holecistektomijami - Haris Topčič, Vilijem; Mlakar, Boštjan (Acta Medico-Biotechnica, 2021)
Purpose: Thorough knowledge about the origin of cystic arteries is very important for carrying out safe laparoscopic cholecystectomy. Numerous studies have tried to classify its origin based on carrying out laparoscopic cholecystectomies. We tested the accuracy of similar studies that classified anatomical variations of the origin of the cystic artery based on laparoscopic cholecystectomies.Methods: We studied the arterial supply to the gallbladder in 220 patients treated by laparoscopic cholecystectomy and compared it with our older study of 81 livers removed from cadavers. We also compared our results with those of similar studies.Results: The study revealed many anatomical variations. Different variations were divided into three groups: Calot’s triangle type, outside Calot’s triangle, and compound type. Some of our results were comparable with other similar studies, but others were not.Conclusion: We found laparoscopic surgery itself to be an unsuitable method for determination of the anatomical origin of cystic arteries.
Keywords: cystic artery; variations; laparoscopic cholecystectomy; corrosion liver casts; cholelithiasis